1993
DOI: 10.1002/ijc.2910540305
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of fgfr4 gene in human breast and gynecological cancers

Abstract: We have investigated gene amplification of fibroblast growth factor receptor-4 (FGFR4) gene in 30 primary breast tumor samples and 15 gynecological tumor samples. Ten percent of the breast tumors showed 2- to 4-fold amplification. Amplification was found more frequently in estrogen- and progesterone-receptor-positive tumors and in tumors with high lymph-node involvement. Breast tumor samples were also analyzed for the amplification of fgfr3 and erbB2 genes and the chromosome 11q13 located genes hst1/int2/bcl1/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
84
0
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(93 citation statements)
references
References 39 publications
5
84
0
2
Order By: Relevance
“…High expression of FGFR4 has been described already for breast cancer (Lehtola et al, 1992;Jaakkola et al, 1993), pancreatic cancer (Leung et al, 1994) and renal cell carcinoma (Takahashi et al, 1999). The cytoplasmic staining of the FGFR4 in melanoma cells is in agreement with other publications investigating the expression for FGFR4 in other types of cancer (Gowardhan et al, 2005;Mawrin et al, 2005).…”
Section: Discussionsupporting
confidence: 90%
“…High expression of FGFR4 has been described already for breast cancer (Lehtola et al, 1992;Jaakkola et al, 1993), pancreatic cancer (Leung et al, 1994) and renal cell carcinoma (Takahashi et al, 1999). The cytoplasmic staining of the FGFR4 in melanoma cells is in agreement with other publications investigating the expression for FGFR4 in other types of cancer (Gowardhan et al, 2005;Mawrin et al, 2005).…”
Section: Discussionsupporting
confidence: 90%
“…20 FGF4 gene amplification has been reported in various human cancers. [24][25][26][27] The FGF4 gene is expressed from the early stage of embryonic development in fetal life and has essential roles in cell differentiation, morphogenesis and proliferation of a variety of organizations. 28 In human adult organs, FGF4 is highly expressed in the testis.…”
Section: Discussionmentioning
confidence: 99%
“…About 10% of breast cancers have been shown to contain amplified levels of the genes for FGFR1 (Adnane et al, 1991;Jacquemier et al, 1994) and FGFR4 (Jaakkola et al, 1993). Jacquemier et al (1994) also reported overexpression of FGFR1 mRNA in 14.5% of breast tumours and Penault-Llorca et al (1995) found both FGFR1 and FGFR4 mRNA to be expressed at high levels in 22% and 32% of breast cancers respectively.…”
Section: Discussionmentioning
confidence: 99%